Refleksije na projekt HiperCatalunya (2003) - Janović, Nikola (Urbani izziv, 2004)
HiperCatalunya (2003) is a futuristic multi-disciplinary project about development futures of the Catalonia region, as a 21st century hyper-territory. The project is conceptualised on an operative methodological framework, which integrates sociological, economic, ecological, architectural and other development strategies. The research results are development proposals, that see territory in dimensions of networked geo-urbanism (new geography and logistics of connecting cities), modernised infrastructure systems (reconstruction of networks and systems: mobility, energy etc.), designing new hyper-realities based on info-structure development (info-leisure-knowledge-tourism multi-development) and hybrid habitats (territorial extension, population, culture).
Keywords: omrežja; prostor; prostorski razvoj; razvojna strategija; regije